Production of Ethylene From Ethanol Dehydration Over H3PO4-Modified Cerium Oxide Catalysts = Penghasilan Etilena Daripada Pendehidratan Etanol Dengan Mangkin Serium Oksida Terubahsuai H3PO4 - Chong, Soo Ling; Soh, Jiah Chee; Cheng, C. K. (Universiti Kebangsaan Malaysia, 2017)
Production of ethylene from ethanol dehydration was investigated over H3PO4 (10 wt.% to 30wt.%)-modified cerium oxide catalysts synthesized by wet impregnation technique. The prepared catalysts were characterized using scanning electron microscope (SEM), N2 adsorption-desorption method, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA) for the physicochemical properties. The ethanol catalytic dehydration was carried out in a fixed-bed reactor at 673-773 K and at ethanol partial pressure of 33 kPa. The effects of phosphorus loading on catalyst and reaction temperatures were investigated in terms of catalytic activity towards product selectivity and yield. Overall, the selectivity and yield of ethylene increased with the temperature and phosphorus loading. The highest ethylene selectivity and yield were 99% and 65%, respectively, at 773 K and 33 kPa over the 30 wt.% H3PO4-modified cerium oxide.